The threat effect of participation in active labor market programs on job search behavior of migrants in Germany - Annette Bergemann; Marco Caliendo; Gerard J. van den Berg; Klaus F. Zimmermann (Institute for Labour Market Policy Evaluation (IFAU), 2011)
Labor market programs may affect unemployed individuals' behavior before they enroll. Such ex ante effects may differ according to ethnic origin. We apply a novel method that relates self-reported perceived treatment rates and job search behavioral outcomes, such as the reservation wage or search intensity, to each other. We compare German native workers with migrants with a Turkish origin or Central and Eastern European (including Russian) background. Job search theory is used to derive theoretical predictions. We examine the omnibus ex ante effect of the German ALMP system, using the novel IZA Evaluation Data Set, which includes self-reported assessments of the variables of interest as well as an unusually detailed amount of information on behavior, attitudes and past outcomes. We find that the ex ante threat effect on the reservation wage and search effort varies considerably among the groups considered.
Keywords: J64; J61; C21; D83; D84; 330; immigrants; policy evaluation; reservation wage; search effort; expactation; unemployment duration; program evaluation; active labor market policy